Efektivitas Metode Pembelajaran Problem Solving terhadap Hasil Belajar Instalasi Penerangan Listrik di SMK Negeri 5 Padang - Santoso, Rachmat Dwi; Sukardi, Sukardi (MASALIQ, 2023)
Learning at SMK Negeri 5 Padang is using conventional methods, in conventional methods teacher dominate more than students, in the learn process like this impact to the results of learning outcomes, the most students can’t reached the Learning Goal Achievement Criteria (KKTP). Problem Solving method expected can solve the problem. The aim this reaserach is determining the effect problem solving method for learning outcomes students. The research uses a type true experimental with pretest-postest control group design. The subject of the research is class XI TITL 2 and XI TITL 3 SMK Negeri 5 Padang. The instrument used is objective test questions. Informations analyze using class completeness testing, effect size and mann whitney test. The result in this research conducted, problem solving method is better more than convensional method. This can be seen by increasing student activity and learning values. That problem solving method effective to used on Electrical Lighting Installation subject in SMK Negeri 5 Padang.